Dietary Plant Extracts Improve the Antioxidant Reserves in Weaned Piglets - Carlo Corino; Michel Prost; Barbara Pizzi; Raffaella Rossi (MDPI AG, 2021)
Reducing the use of antibiotics in livestock in order to contain antibiotic resistance and studying natural substance additives are key to sustainability. Among the various biological activities of plant extracts, antioxidant activity plays an important role. The present study assesses the total antioxidant activity and antioxidant reserves using the Kit Radicaux Libres test (KRL™ Kirial International, Couternon, France). One hundred and sixty piglets (Topics × Tempo) weaned at 28 days of age were divided into four dietary treatment groups that were fed a commercial diet (the control group, C); 500 mg/kg Boswellia extract (BOS); 200 and 50 mg/kg Uncaria and Tanacetum extracts (UT) respectively; and 225 mg/kg of an antioxidant plant extract mixture (AOX). The blood antioxidant activity of the piglets was measured using the KRL test and the reserves were analyzed on whole blood samples after hydrolysis with glucosidase, sulfatase and glucuronidase. No significant differences were observed in growth performance. The delta KRL values of the whole blood showed a significantly higher total antioxidant status of the piglets from the BOS and AOX groups than the UT and C groups (+30.7 BOS; +27.7 AOX vs. +17.81 UT +13.30 C; p = 0.002) between 18 and 28 days post-weaning. The delta KRL values of red blood cells (RBCs) showed a significantly higher total antioxidant status of the piglets from the AOX groups than the UT and BOS groups (+22.2 AOX; vs. +9.90 UT +9.4 BOS; p = 0.016) between the two sampling times. Reserves of UT and AOX were higher than C and BOS for all enzymes, glucosides, sulphates, and glucuronides. The biological KRL test proved to be an extremely sensitive tool to evaluate the piglets' antioxidant status. Determining the antioxidant reserve also provides a better understanding of the real antioxidant status of pigs.